Pinniped electroencephalography: Methodology and findings in California sea lions (Zalophus californianus) - Williams, D. Colette; Haulena, Martin; Dennison, Sophie; Waugh, Lynnette; Goldstein, Tracey; Nutter, Felicia; Bonn, Bill Van; Hoard, Vanessa; Laxer, Kenneth D.; Buckmaster, Paul S.; Gulland, Frances M. D.; Tharp, Barry (Frontiers in Veterinary Science, 2023)
Word count: 182 This study was designed to identify abnormalities in the electroencephalograms (EEG) recorded from stranded California sea lions (Zalophus californianus) with suspected domoic acid (DA) toxicosis. Recordings from animals presenting for non-neurological issues were also obtained to better understand the normal EEG (background activity and transient events) in this species, as to date studies have focused on examining natural sleep in pinnipeds. Animals were sedated for electrode placement and EEG acquisition with some receiving antiepileptic medications or isoflurane during the procedure. Recordings were read and scored from 0 (normal) to 3 (severely abnormal). Epileptiform discharges, consisting of spikes, sharp waves, slow waves and/or spike-waves, were present in all EEGs with scores of 1, 2 or 3. Event distribution varied: generalized, lateralized, multifocal, bifrontal, bioccipital and/or bitemporal discharges were found between sea lions and occasionally within the same EEG on a given sea lion. No clinical seizures were observed during recording but a few sea lions had findings consistent with electroencephalographic seizures. When available, supporting diagnostic results, magnetic resonance imaging and histopathology, were described, as well as, the status of those released with satellite tags.